Supramolecular recognition of phosphocholine by an enzyme-like cavitand receptor. Issue 4 (12th December 2019) - Legnani, Laura; Puglisi, Roberta; Pappalardo, Andrea; Chiacchio, Maria Assunta; Trusso Sfrazzetto, Giuseppe
Abstract : The first supramolecular receptor for phosphocholine, able to detect ppb levels of the guest with high efficiency ( K up to 10 7 M −1 ) and selectivity, is reported here. Abstract : The first example of supramolecular recognition of phosphocholine by a cavitand receptor has been reported here. The chemical structure of the receptor has been optimized by DFT calculations. The recognition mechanism is based on a "multi-topic approach", which leads to highly efficient ( K value up to 10 7 M −1 ), selective and sensitive (ppb level) sensing of phosphocholine. The recognition mechanism proposed here is similar to those exploited by Nature, and paves the way for the realization of new sensors with important applications in medicine and security fields.